The Antibacterial Potential of Ethanol Extract from Banana Peel (Musa Paradisiaca) on the Growth of Staphylococcus aureus and Streptococcus pneumoniae - Darnedy Fatwa Mely Santy; Qori Fadillah*; Riyani Susan Bt. Hasan; Juliana Lina (Riwayat: Educational Journal of History and Humanities, 2023)
Staphylococcus aureus and Streptococcus pneumoniae are the most common bacterial infections in humans. Efforts to control using penicillin antibiotics tend to cause resistance and side effects, so people prefer to overcome them by self-medication or using traditional ingredients such as banana peels. This study aims to determine whether there is antibacterial activity of kepok banana peels against Staphylococcus aureus and Streptococcus pneumoniae bacteria. Methods: This research is an experimental study with the type of Post Test Only Control Group Design with the well method. Results: The average diameter of the inhibition zone on Staphylococcus aureus was 7,60 mm, 6,43 mm and 5,33 mm at concentrations of 100%, 75% and 50% respectively. And the average diameter of the inhibition zone on Streptococcus pneumoniae was 7,78 mm, 6,61 mm and 5,46 mm at concentrations of 100%, 75% and 50% respectively. Conclusion: The antibacterial potential of kepok banana peel extract at the overall concentration and the most optimal concentration is 100% where the diameter of the inhibition zone in Staphylococcus aureus is 7,60 mm and in Streptococcus pneumoniae is 7,78 mm.